Climatic changes on Szczecin Seashore and their impact on river flow volumes - Świątek, Małgorzata (Bulletin of Geography. Physical Geography Series, 2017)
The analysis of variability of temperature and precipitation on following station: Szczecin, Świnoujście, Resko and Kołobrzeg, as well as the study of river flows in the Ina and Rega Rivers in Goleniów, Resko and Trzebiatów in 1955-2014 years has been made. Data was provided by IMGW-PIB. The correlation an regression analysis have been used. The conducted research demonstrated that the average year, spring and summer air temperature on Szczecin Seashore rises. Precipitation totals remain basically unchanged. They grow a little in February and in March. No significant changes of river flows occurred in the course of the examined sixty-year period. Flows in the Ina River rose slightly in February and in September and they diminished in the Rega River in October. Long-term variability of river flows is more strongly affected by the variability of precipitation totals rather than by the variability of air temperature. The variability of flows correlates the strongest with the variability of precipitation totals in March, April and in November, while the influence of precipitation in a preceding month on river flows is the most evident in spring and autumn.